Населення черняхівської культури, поховане на могильнику біля с. Велика Бугаївка, за матеріалами краніології - Рудич, Т.О. (Археологія і давня історія України, 2021)
У статті дано інформацію про краніологічний матеріал із розкопок могильника черняхівської культури біля с. Велика Бугаївка та проаналізовано склад похованого тут населення. Cemetery of Chernyakhiv culture near the Velyka Buhaivka village was excavated in 1995—2005 by an expedition of O. V. Petrauskas and R. G. Shishkin. During the excavations the anthropological material was obtained. The male series is characterized by a medium-long, narrow, medium-high, dolichocranial cranium. The face is short, narrow, mesognathic. Horizontal face profiling is sharp. Orbits are medium high, the nose is medium wide. The angle of the nasal bones is on the border of medium and large values. The nose is of medium height. According to the results of statistical analysis, the group from Velyka Buhaivka is close to the series from the cemeteries of Romashki, Kurnyky, Ranzheve. The group is closer to the series of Welbark culture Maslomench, Grudek, a bit closer to the Welbark mixed series of the Lower Vistula, than to individual series of Chernyakhiv culture from the territory of Ukraine. The female group is characterized by a long, medium- wide on the border with a wide, medium-high, dolichokranny cranium. The face is medium-wide and medium-high, orthognathic. The orbits were medium high, the nose was medium wide. Horizontal profiling of the face at the upper level is on the border of sharp and moderate, its profiling at the zygomaxillary level is sharp. The angle of the nasal bones is medium, the epiglottis is medium high. According to the results of the analysis, the women’s series from Velyka Buhaivka is closest to the women from Chernyakhiv, Zhuravka, Popivka. From the groups of Polish Welbark culture the mixed group of Slovinsko-Drawska is close to the women from Velyka Buhaivka. The dolichocranium narrow-faced type was dominant in people buried by inhumation. It is recorded in the people buried in the graves accompanied by the grave goods of the phase C₂, C₂—C₃, D₁. This type is present both in burials directed with the head to the North, and to the West.